The presequence pathway is involved in protein sorting to the mitochondrial outer membrane - Wenz, Lena-Sophie (BlackWell Publishing Ltd, 2014)
The mitochondrial outer membrane contains integral α-helical and β-barrel proteins that are imported from the cytosol. The machineries importing β-barrel proteins have been identified, however, different views exist on the import of α-helical proteins. It has been reported that the biogenesis of Om45, the most abundant signal-anchored protein, does not depend on proteinaceous components, but involves direct insertion into the outer membrane. We show that import of Om45 occurs via the translocase of the outer membrane and the presequence translocase of the inner membrane. Assembly of Om45 in the outer membrane involves the MIM machinery. Om45 thus follows a new mitochondrial biogenesis pathway that uses elements of the presequence import pathway to direct a protein to the outer membrane.